2020
DOI: 10.1007/s00062-020-00938-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Imaging Grading Biomarker for Predicting Hearing Loss in Acoustic Neuromas

Abstract: The aim of this study was to investigate an imaging biomarker based on contrast enhanced T1-weighted and T2-weighted magnetic resonance imaging (MRI) to determine the hearing loss related to acoustic neuromas (AN). Methods In this retrospective study, 441 acoustic neuromas treated with microsurgery were included. The diagnostic and follow-up MRI and audiometry of these patients were compared. Results We discovered a new MRI grading biomarker based on the percentage of tumor filling the inner auditory canal (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Classification by size was based on the Koos grading system from grades I to IV as follows: grade I, a small intracanalicular tumor; grade II, a small tumor with protrusion into the CPA cistern; grade III, a tumor occupying the CPA cistern with no brainstem displacement; and grade IV, a large tumor with brainstem and cranial nerve displacement. IAC invasion was classified by TFIAC (tumor filling inner auditory canal) as follows: grade I, 0% < TFIAC ≤ 25%; grade II, 25% < TFIAC ≤ 50%; grade III, 50% < TFIAC ≤ 75%; grade IV, 75% < TFIAC ≤ 100% ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Classification by size was based on the Koos grading system from grades I to IV as follows: grade I, a small intracanalicular tumor; grade II, a small tumor with protrusion into the CPA cistern; grade III, a tumor occupying the CPA cistern with no brainstem displacement; and grade IV, a large tumor with brainstem and cranial nerve displacement. IAC invasion was classified by TFIAC (tumor filling inner auditory canal) as follows: grade I, 0% < TFIAC ≤ 25%; grade II, 25% < TFIAC ≤ 50%; grade III, 50% < TFIAC ≤ 75%; grade IV, 75% < TFIAC ≤ 100% ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“… 4 Affected/normal side of IAC was determined as distance from the nasal crest to the dorsal crest of the IAC at the affected/normal side. Expansion of affected side of IAC was determined as the ratio of distance of the affected side to distance of the healthy side and those above were measured on temporal bone CT. 10 …”
Section: Methodsmentioning
confidence: 99%
“…As noted in a recent report, Zhou et al proposed a new MRI grading biomarker based on the percentage of tumor filling the inner auditory canal (TFIAC) to predict the hearing loss in SVS and defined the four grades accordingly with low TFIAC (<25%) in Grade I and high TFIAC in Grade IV (>75%). They found that the patients in TFIAC grade III experienced more significant hearing deterioration than Grade I patients, and TFIAC grade IV patients also had a higher rate of non-serviceable hearing (56). Besides, in another MRI study aiming to identify practical predictors of hearing loss in the conservatively managed SVS, the researchers considered the fundal cap as a candidate.…”
Section: Pressure and Tumor Filling Within Iacmentioning
confidence: 99%